Designing for Dissemination Among Public Health Researchers: Findings From a National Survey in the United States - Brownson, Ross C.; Jacobs, Julie A.; Tabak, Rachel G.; Hoehner, Christine M.; Stamatakis, Katherine A. (American journal of public health (1971), 2013)
Objectives. We have described the practice of designing for dissemination among researchers in the United States with the intent of identifying gaps and areas for improvement. Methods. In 2012, we conducted a cross-sectional study of 266 researchers using a search of the top 12 public health journals in PubMed and lists available from government-sponsored research. The sample involved scientists at universities, the National Institutes of Health, and the Centers for Disease Control and Prevention in the United States. Results. In the pooled sample, 73% of respondents estimated they spent less than 10% of their time on dissemination. About half of respondents (53%) had a person or team in their unit dedicated to dissemination. Seventeen percent of all respondents used a framework or theory to plan their dissemination activities. One third of respondents (34%) always or usually involved stakeholders in the research process. Conclusions. The current data and the existing literature suggest considerable room for improvement in designing for dissemination.